Influence of fins on the absorber plate of tubular solar still- An experimental study. (2021) - Sathyamurthy, Ravishankar; Mageshbabu, D.; Madhu, B.; Muthu Manokar, A.; Rajendra Prasad, A.; Sudhakar, M.
Abstract: This study emphasizes the importance of adding fins to the flat absorber plate to augment the thermal performance and yield of potable water produced. The potable water produced from both solar still were compared by considering the similar climatic condition. The results showed that the addition of fins in the absorber plate augments the water temperature and thereby the rate of evaporation from the surface. Linear regression between the experimental and predicted yield was carried out. It was clear that the observed and predicted yield have a deviation of about ± 5%. The total yield produced from the modified absorber was improved by about 46.85% than conventional tubular solar still. Also, results of thermal efficiency exhibited that the solar still using finned absorber was increased while compared to the tubular solar still without fins.